2015
DOI: 10.1039/c5ra11325c
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model estimation of guest diffusion in metal–organic frameworks (MOFs)

Abstract: An analytical model was developed to efficiently and accurately estimate the guest diffusivity in flexible metal–organic frameworks (MOFs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…38 Zheng et al reported recently an alternate approach to extract the energy profile from DFT calculations. 39 Last, Chmelik and Karger analyzed experimentally measured transport and Stefan-Maxwell diffusivities of various guest molecules in ZIF-8 with a TST theory-based model and showed a profound agreement on the concentration dependency of diffusivities. 40 Umbrella sampling is a biased sampling method, involving a reaction coordinate (RC) connecting the two cages related to the jump under study.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…38 Zheng et al reported recently an alternate approach to extract the energy profile from DFT calculations. 39 Last, Chmelik and Karger analyzed experimentally measured transport and Stefan-Maxwell diffusivities of various guest molecules in ZIF-8 with a TST theory-based model and showed a profound agreement on the concentration dependency of diffusivities. 40 Umbrella sampling is a biased sampling method, involving a reaction coordinate (RC) connecting the two cages related to the jump under study.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…There are numerous approaches reported in the literature for handling the rate calculation, from which we chose to follow the energy profile mapping along the diffusion path, as has been used for benzene in silicalite-1 by Forester and Smith and Kolokathis et al and for various gases in ZIF-8 by Verploegh et al This is usually achieved by the umbrella sampling technique . Zheng et al reported recently an alternate approach to extract the energy profile from DFT calculations . Last, Chmelik and Kärger analyzed experimentally measured transport and Stefan-Maxwell diffusivities of various guest molecules in ZIF-8 with a TST theory-based model and showed a profound agreement on the concentration dependency of diffusivities …”
Section: Simulation Methodologymentioning
confidence: 99%
“…4,8 Concurrently, an abundance of theoretical methods and models for diffusion computation have been developed. 5,7,[9][10][11] For zeolitic imidazolate framework 8 (ZIF-8) in particular, 12 two trends of note in guest diffusion have been reported in experiments and simulation. 4,10,11,13,14 First, guests with an alkene skeleton diffuse faster than those with an alkane skeleton.…”
Section: Introductionmentioning
confidence: 94%
“…5,7,[9][10][11] For zeolitic imidazolate framework 8 (ZIF-8) in particular, 12 two trends of note in guest diffusion have been reported in experiments and simulation. 4,10,11,13,14 First, guests with an alkene skeleton diffuse faster than those with an alkane skeleton. Chmelik et al 4 measured the self-diffusion of ethene and ethane in ZIF-8 and found that the former diffuses 5.5 times faster than the latter due to its smaller kinetic diameter, which increases the hopping rate of adsorbates from cage to cage and then enhances the diffusion rate.…”
Section: Introductionmentioning
confidence: 94%
“…The data shown in Figure c essentially provides a snapshot in time of metalation; concentration profiles like this one can be used to estimate diffusivity constants starting from Fick’s laws. , Such analysis has been performed for porous materials, for example, on methanol diffusion through porous materials, and exponential-like profiles were observed . A model to adequately describe the concentration profile of Figure c would require knowing the surface permittivity of UiO-67 (which would include the kinetics associated with surface barriers) and the equilibrium binding kinetics of the Pt precursor to the bipyridine sites.…”
Section: Resultsmentioning
confidence: 99%